Advanced bioscience and AI: debugging the future of life. Issue 6 (11th October 2019) - Lawrence, David R.
Abstract : Scientific advancements lead us towards a future in which Homo sapiens may no longer be the only sapient being. The societal and legal challenges of this potentiality are immense, and it will require traditionally disparate branches of science to recognise their similarities in order to address them effectively.